The Effect of Murottal Al-Quran Therapy on Pain in Post Cesarean Surgery Patients at Abby Mother and Child Hospital, Lhokseumawe City - Anna Millizia; Mardiati; Anita Syafridah (Arkus, 2022)
Pain is an unpleasant sensory and emotional experience resulting from actual or potential tissue damage or described in terms of the damage. Murottal is a recording of the voice of the Qur'an sung by a qori (reader of the Qur'an). In this study, the degree of pain before murottal therapy was obtained based on the NRS (numeric rating scale) pain measuring instrument by the respondents, it was found that 8 patients (18.6%) had normal pain levels, 23 people (53.5%) experienced mild pain. ), and 12 people (27.9%) experienced moderate pain. Meanwhile, after murottal therapy based on the NRS pain measuring instrument (Numeric Rating Scale) by the respondents, it was found that patients with normal pain levels increased to 28 people (65.1%), and those who experienced mild pain became 15 people (34.9%). There is an effect of murottal Al-Qur'an therapy in lowering the pain intensity in post-cesarean patients at RSIA Abby, Lhokseumawe City